Human papillomavirus vaccine coverage in Rwanda: A population-level analysis by birth cohort. Issue 24 (19th May 2020) - Sayinzoga, Felix; Umulisa, M. Chantal; Sibomana, Hassan; Tenet, Vanessa; Baussano, Iacopo; Clifford, Gary M.
Highlights: 1, 156, 863 girls received first dose HPV vaccine between 2011 and 2018 in Rwanda. An initial school-grade-targeted catch-up transited to routine 12 yrs vaccination. Census-level coverage was 10–40% for girls born in 1993–1995, 50–65% for 1996–2000. Census-level coverage was 80–90% for 2001–2006 cohorts vaccinated at 12 years. Birth cohorts provide clearer picture of HPV vaccine coverage in Rwanda. Abstract: Background: In 2011, Rwanda became the first African nation to implement a national human papillomavirus (HPV) vaccination program, conceived to protect girls aged <15 years (i.e. born ≥1997). After an initial school-grade-targeted catch-up campaign, there was a transition to routine vaccination of 12 year-olds only. We aimed to produce population-level vaccine coverage estimates. Methods: The Rwandan Expanded Program on Immunization (EPI) collected data on number of eligible girls and HPV vaccines delivered, stratified by calendar year (2011–2018), girl's age, district and vaccination round. HPV vaccine coverage was estimated by birth cohort (reconstituted using calendar year and age), as a proportion of (1) eligible target, and (2) the 2012 Rwandan census population. Results: 1, 156, 863 girls received first dose of HPV vaccine between 2011 and 2018, corresponding to 98% of the eligible target. Median vaccination age was 15 years (interquartile range [IQR] 13–16) in 2011–2013 (school grade-targeted catch-up), 13 years (IQR 12–14) in 2014 (transition) and 12 years in 2015–2018 (routine). Population-level coverage versus the census increased from 10 to 40% for girls born in 1993–1995 (median vaccination age = 17 years) to 50–65% for 1996–2000 birth cohorts (14 years), and 80–90% for 2001–2006 birth cohorts (12 years). Coverage trends were similar across provinces and in the capital, Kigali. Second and third round coverage suggested most vaccinated girls completed their recommended dosing regimen (which reduced from 3 to 2 doses in 2015). Conclusions: Birth cohorts provide a clear picture of population-level HPV vaccine coverage after a pragmatic catch-up campaign, particularly in Rwanda where eligible school grades included wide age ranges. Whilst the catch-up campaign resulted in some coverage gaps in out-of-school teenagers, coverage remains high in cohorts routinely targeted as 12 year-olds.